2005
DOI: 10.1177/154193120504901011
|View full text |Cite
|
Sign up to set email alerts
|

Factors Contributing to Airport Screener Expertise

Abstract: An airport X-ray Screener Test Battery was developed to better understand how selected aspects of screeners' visual and perceptual capabilities, attentional and verbal processing, work schedule, medication use, work history, training, equipment knowledge, personal style, attitudinal characteristics, and job satisfaction are related to job performance. The Test Battery was administered to 92 X-ray screeners and analyses compared Test Battery performance with X-ray screening job performance. Analyses suggest tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Five scores were submitted for MINRES factor analysis with varimax rotation (Harman, 1975; Jöreskog, 2003): COR and the WR from the first and second administrations, and “Time” in months between administrations. Time serves to capture the “linear trend” (Anderson, 1963, p. 2) associated with months between first and second test administrations and follows a history of related factor-analytic practice (McCallum et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five scores were submitted for MINRES factor analysis with varimax rotation (Harman, 1975; Jöreskog, 2003): COR and the WR from the first and second administrations, and “Time” in months between administrations. Time serves to capture the “linear trend” (Anderson, 1963, p. 2) associated with months between first and second test administrations and follows a history of related factor-analytic practice (McCallum et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Five scores were submitted for MINRES factor analysis with varimax rotation (Harman, 1975;Jöreskog, 2003): COR and the WR from the first and second administrations, and "Time" in months between administrations. Time serves to capture the "linear trend" (Anderson, 1963, p. 2) associated with months between first and second test administrations and follows a history of related factor-analytic practice (McCallum et al, 2005). Harman (1975), it is noteworthy, speaks to the essential equivalence of MINRES to earlier methods (i.e., iterated principal factors analysis); whereas Jöreskog discusses both its distributional robustness and its further equivalence to one of the component analyses of LISREL.…”
Section: Factor Analysismentioning
confidence: 99%
“…When available, T&E results for previous systems can provide critical inputs, but if unavailable, a functional T&E of the spectrum of subsystems or components of one or more target systems or products may be performed instead and then combined with a literature-based approach to address the shortfall (e.g., Bittner, Wiker, Bramwell, & Kinghorn, 1994;Bittner, Wiker, Kinghorn, & Bramwell, 1993). Incident, accident, and performance error information also may contribute to the requirements development processes (e.g., Hanowski, Bittner, Knipling, Byrne, & Parasuraman, 1995;Kantowitz & Bittner, 1992;McCallum et al, 2005). Very early design T&E, particularly as a multiperson or multidiscipline process, can provide a critical examination of the emerging or proposed requirements themselves (Bittner, 1993).…”
Section: Testing and Evaluationmentioning
confidence: 99%
“…Recently, TIP has been used to assess the relationship between screener performance and a variety of factors (e.g., capabilities, skills, knowledge, attitudes, background, and job factors; McCallum et al, 2005). Results of McCallum et al's (2005) study indicate that factors such as time on the job and less medication use are related to higher perfor-mance in the TIP scenarios.…”
Section: Detectionmentioning
confidence: 99%
“…Results of McCallum et al's (2005) study indicate that factors such as time on the job and less medication use are related to higher perfor-mance in the TIP scenarios. McCallum et al (2005) suggested that studies such as these can help to improve the selection and training of screeners.…”
Section: Detectionmentioning
confidence: 99%